The Fruticose Lichens In The Forest Tahura (Taman Hutan Raya) R. Soeryo, East Java - Miftahul Islam Jannah; Dwi Anggorowati Rahayu; Murni Sapta Sari; Ludmilla Fitri Untari (Biotropika: Journal of Tropical Biology, 2019)
A taxonomic study of the fructicose lichens in the forest of Tahura (Taman Hutan Raya) R. Soeryo had been conducted based on morphological, anatomical and chemical characters. In this research involved a method of descriptive explorative and the aim of this research is to identify and determine of fructicose lichens in the forest of Tahura R. Soeryo. Eleven species of fructicose lichen are reported for the firt time from the forest of Tahura R. Soeryo. They are Evernia prunastri, Ramalina calicaris, Teloschistes flavicans U. glabrescens, , U. subfloridana, U. Ceratina, U. floridana,U. hirta and three species were found as new records in Java are Usnea esperantiana, U. flammea, and U. strigosa . Taxonomic descriptions and figures are presented in the articel.